Effect of Wigner energy on the symmetry energy coefficient in nuclei - 田俊龙 崔海涛 高腾 王宁 (Chinese physics C, 2016)
The nuclear symmetry energy coefficient（including the coefficient asym^（4） of the I^4 term） of finite nuclei is extracted by using the differences of available experimental binding energies of isobaric nuclei.It is found that the extracted symmetry energy coefficient asym^＊（A,I） decreases with increasing isospin asymmetry I,which is mainly caused by Wigner correction,since esym^＊ is the summation of the traditional symmetry energy esym and the Wigner energy ew.We obtain the optimal values J = 30.25±0.10 MeV,ass=56.18±1.25 MeV,asym^（4） = 8.33±1.21 MeV and the Wigner parameter x= 2.38 ±0.12 through a polynomial fit to 2240 measured binding energies for nuclei with20 ≤ A ≤ 261 with an rms deviation of 23.42 keV.We also find that the volume symmetry coefficient J≌ 30 MeV is insensitive to the value x,whereas the surface symmetry coefficient ass and the coefficient asym^（4） are very sensitive to the value of x in the range 1≤x≤4.The contribution of the asym^（4） term increases rapidly with increasing isospin asymmetry I.For very neutron-rich nuclei,the contribution of the asym^（4） term will play an important role.